Organizational Process Factors As Supporting Employee Performance In The Banjarbaru City Regional District Office - Roro Rukmini Widiaswari (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
The purposes of this study are 1) To describe the performance of the employees at the Banjarbaru District Head Office based on the factors that influence it; 2) To find out the efforts made by the Banjarbaru District Head to improve the performance of his employees. The results showed that the majority of the employees at the Banjarbaru Camat Office were still non-civil servants with a percentage of 48% and another 52% were civil servants. Referring to the research topic, basically, all indicators that affect employee performance which are used as indicators in measuring performance are indicators that are interrelated and mutually supportive, it's just that there are several factors that do not really affect the performance of employees when they are given assignments. or in acting as an employee.